2020
DOI: 10.1159/000511759
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Manifestations among Patients with Rheumatic Diseases

Abstract: <b><i>Background:</i></b> Rheumatic diseases have many hematological manifestations. Blood dyscrasias and other hematological abnormalities are sometimes the first sign of rheumatic disease. In addition, novel antirheumatic biological agents may cause cytopenias. <b><i>Summary:</i></b> The aim of this review was to discuss cytopenias caused by systemic lupus erythematosus and antirheumatic drugs, Felty’s syndrome in rheumatoid arthritis, and autoimmune hemolytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
9

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 76 publications
2
32
0
9
Order By: Relevance
“…Shanmugam et al demonstrated anti-phospholipid antibodies and genetic prothrombotic conditions in a high percentage of patients with lower extremity ulcers [34]. According to Klein and colleagues, patients may also develop a hypercoagulable state with a predisposition to thromboembolic events related to underlying neutropenia and leukopenia [35]. At the same time, certain antirheumatic drugs can cause leukopenia [36].…”
Section: Discussionmentioning
confidence: 99%
“…Shanmugam et al demonstrated anti-phospholipid antibodies and genetic prothrombotic conditions in a high percentage of patients with lower extremity ulcers [34]. According to Klein and colleagues, patients may also develop a hypercoagulable state with a predisposition to thromboembolic events related to underlying neutropenia and leukopenia [35]. At the same time, certain antirheumatic drugs can cause leukopenia [36].…”
Section: Discussionmentioning
confidence: 99%
“…Jenis infeksi yang paling umum yakni infeksi bakteri pada kulit dan saluran pernapasan oleh Staphylococcus aureus, Streptococcus, Herpes zoster, bakteri gram negatif, dan jamur. 7,8 Gejala sistemik seperti demam dan berat badan turun juga dapat ditemukan. Pasien dapat mengeluh nyeri kuadran kiri atas abdomen karena infark limpa atau distensi kapsular kalenjar limpa.…”
Section: Diagnosis Tanda Dan Gejalaunclassified
“…Laju endap darah (LED) dan C-Reactive Protein (CRP) juga ditemukan meningkat. 3,6,7,9 Temuan laboratorium dari artritis reumatoid, seperti FR positif dan anti-CCP, hampir selalu ada pada kasus sindrom Felty. Anti-CCP memiliki spesifisitas yang sangat tinggi untuk artritis reumatoid.…”
Section: Diagnosis Tanda Dan Gejalaunclassified
See 2 more Smart Citations